Study guides

Q: Solve using substitution x plus y equals 3 and y equals 9?

Write your answer...

Submit

Related questions

You'd need another equation to sub in

-2

(2,3)

x = -2 and y = 1

It is not possible to do so because the question contains one equation (5x + y = 1) and one expression (3x + 2y + 2). An expression cannot be solved.

When using substitution the answer to y0.5x plus 2 -y-2x plus 4 is y = -2 (x-1.

Solve using the quadratic formula

If you mean: x+7y = 7 and 2x+y = 8 Then by substitution: x = 49/13 and y = 6/13

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3

a=5: c=4

a2+30a+56=0 , solve for a Using the quadratic formula, you will find that: a=-2 , a=-28

There is no symbol between 7x and 31. Please resubmit using words eg "plus", "equals" etc.

If you mean: x+7y = 39 and 3x-2y = 2 Then by substitution: x = 4 and y = 5

the answer

(2,-2)

How do you solve 4y plus x equals 8

This is not Calculus.y=7(Already solved)substiute y=7 into y=8xtherefore 7 = 8xtherefore x = 7/8

One way to solve this system of equations is by using matrices. Form an augmented matrix in which the first 2x2 matrix is the coefficient matrix and the 2x1 matrix on its right is the answer. Now apply Gaussian Elimination and back-substitution. Using this method gives x=5 and y=1.

Yes its on the line.

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

-2 plus 5 equals +3

2x-3y=13

From second equation: y = 8 + 2xSubstitute for y in first equation: 3x + 16 + 4x = 2ie 7x = -14ie x = -2 and y = 4

From first equation: y = 5 - 5xSubstitute for y in second equation: 3x + 10 - 10x = 3ie -7x = -7ie x = 1 and y = 0

By elimination: x = 3 and y = 0